2017
DOI: 10.2495/cmem-v6-n2-411-422
|View full text |Cite
|
Sign up to set email alerts
|

Particle image velocimetry measurements of stratified gas-liquid flow in horizontal and inclined pipes

Abstract: The main objectives of this work is to produce detailed velocity profile measurements over a range of operating conditions of two phase gas/liquid flow with low liquid fractions in horizontal and inclined pipes. The experiments are performed in a 15 m long stainless steel pipe section with internal diameter 56 mm at room temperature and atmospheric outlet pressure. Exxsol D60 oil (viscosity 1.30 mPa s, density 793 kg/m 3), water (viscosity 0.89 mPa s, density 999 kg/m 3) and air (viscosity 0.018 mPa s, density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The interfacial shear, pressure fluctuations, turbulent fluid motion, and other effects observed in gas‐liquid flows produce interfacial instabilities and wave structure formation. A number of the PIV studies for gas‐liquid flows have reported difficulty in defining the precise position of the interface and in taking measurements close to pipe walls due to reflection at the interface and wall respectively . Various techniques have been employed to improve PIV measurements at the interface such as camera orientation, optical filters, fluorescent seeding, and the use of complementary measurement instrumentations such as pulsed shadow technique (PST) and planar laser‐induced fluorescence (PLIF) among others .…”
Section: Piv Measurements Of Two‐phase Flow Characteristics Of Gas‐limentioning
confidence: 99%
“…The interfacial shear, pressure fluctuations, turbulent fluid motion, and other effects observed in gas‐liquid flows produce interfacial instabilities and wave structure formation. A number of the PIV studies for gas‐liquid flows have reported difficulty in defining the precise position of the interface and in taking measurements close to pipe walls due to reflection at the interface and wall respectively . Various techniques have been employed to improve PIV measurements at the interface such as camera orientation, optical filters, fluorescent seeding, and the use of complementary measurement instrumentations such as pulsed shadow technique (PST) and planar laser‐induced fluorescence (PLIF) among others .…”
Section: Piv Measurements Of Two‐phase Flow Characteristics Of Gas‐limentioning
confidence: 99%
“…The two-phase flow measurements indicated expected behaviour for low flow rates, and very interesting features related to the turbulence structure at higher flow rates that led to wavy interfaces. Inspired by ongoing approach, Vestøl et al [24] produced detailed velocity profile measurements over a range of operating conditions of two phase gas/liquid flow with low liquid fractions in horizontal and inclined pipes. The experiments were implemented in a 15 long stainless steel pipe with internal diameter of 56 at room temperature and atmospheric outlet pressure.…”
Section: Introductionmentioning
confidence: 99%